FAKTOR YANG MEMPENGARUHI KINERJA PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Aril Suryadi, FX Tjakrawala Kurniawan (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
This research was conducted to determine whether the company's growth, leverage affects the performance of companies in manufacturing sector companies listed on the Indonesia Stock Exchange, especially in 2013-2017. The number of samples used amounted to 115 data determined using purposive sampling, sample data obtained in the form of financial statements found at www.idx.co.id. The data in this study were processed with program eviews 10.0 by conducting descriptive statistical tests, common tests, fixed tests, random tests and hypothesis tests. Company growth has a significant positive effect on company performance with company size as a moderating variable, while leverage has a significant negative effect on company performance with company size as moderation.